Higher order duality in multiobjective fractional programming problem with generalized convexity - JOSHI, Bhuwan Chandra (Yugoslav Journal of Operations Research; Vol 27 No 2 (2017), 2017)
We have introduced higher order generalized hybrid B-(b;ρ ; θ; ~p; ~r)-invex function. Then we have established higher order weak, strong and strict converse duality theorems for a multiobjective fractional programming problem with support function in the numerator of the objective function involving higher order generalized hybrid B - (b; ; ; ~p; ~r)-invex functions. Our results extend and unify several results from the literature. Keywords: Multiobjective fractional programming, Support function Duality Higher order B - (b;ρ ;θ ; ~p; ~r)-invex function.